PENGARUH SLOW-STROKE BACK MASSAGE DENGAN MINYAK ESENSIAL YLANG-YLANG (Cananga odorata) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Handayani, Rahajeng (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Hypertension is a major risk factor for cardiovascular disease is the leading cause of death in the elderly population in Indonesia. Objective of this research was to analyze the effect of slow-stroke back massage with ylang-ylang ( Cananga odorata ) essential oils to decrease blood pressure in elderly with hypertension in PSTW Jara Mara Pati Singaraja. Design of this research was a pre-experimental with one-group pretest-posttest approach. Sample consisted of 30 respondents with a total sampling technique. The results of the analysis with the Wilcoxon test showed that blood pressure significantly decrease in elderly with hypertension after treatment of slow-stroke back massage with ylang-ylang essential oils with value of ? = 0.000 is less than ? = 0.05. Based on the result, slow - stroke back massage with ylang - ylang essential oils can be used as an independent nursing intervention and safe therapy and effective in lowering blood pressure in elderly with hypertensive . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Elderly Hypertension; Slow-stroke back massage; Ylang-ylang essential oils